Application of Student Facilitator and Explaining Learning Model to Increase Student Activeness and Learning Outcomes - Nadia Hesti Anggraini; Siti Awaliyah; Edi Suhartono (Edunity Kajian Ilmu Sosial dan Pendidikan, 2024)
Education is the process of changing the attitudes and behaviors of an individual or a group of people to mature humans through teaching and training. Education can be realized through formal teaching in schools by teachers or at home by parents. In school, students are trained to express their opinions more confidently, take responsibility, and learn to develop their potential. The Pancasila and Citizenship Education at SMK Negeri 2 Kediri is one of the subjects that requires students to be active and brave in expressing their opinions. However, in reality, many students are passive in learning. Moreover, in terms of student learning outcomes, many students' achievements fall below the minimum passing criteria. Therefore, this research applies the Student Facilitator and Explaining (SFAE) learning model to improve student engagement and learning outcomes. The stages of the SFAE learning model include 1) teaching, 2) teams, 3) student creative, 4) student explaining, 5) whole class consisting of 23 units. This research is action research using two cycles. The results show an improvement in student engagement and learning outcomes after implementing the learning model. In terms of student engagement, the results of the first cycle show a percentage of 65.89; then, it increased in the second cycle to 83.75. As for learning outcomes, the first cycle shows an average score of 64.29; it then increased in the second cycle to 85.71. This improvement indicates that the implementation of the Student Facilitator and Explanation learning model can enhance student engagement and learning outcomes.